The Staged ligation of hemorrhoids.: Our Experience. Preliminary report. - Estefan, Alberto; Grezzi, Roberto; Esperón, Ruben; Cardozo, Tabaré; Pérez Penco, Ernesto (Cirugía del Uruguay, 1981)
The authors· describe a new technique for treatment of hemorrhoids which consists in staged Jigation, and report results obtained in 24 cases.